4Pi microscopy reveals an impaired three-dimensional mitochondrial network of pancreatic islet beta-cells, an experimental model of type-2 diabetes - Dlasková, Andrea; Špaček, Tomáš; Šantorová, Jitka; Hlavatá, Lydie; Berková, Zuzana; Saudek, František; Lessard, Mark; Bewersdorf, Joerg; Ježek, Petr (Biochimica et biophysica acta, 2010)
Insulin production in pancreatic beta-cells is critically linked to mitochondrial oxidative phosphorylation. Increased ATP production triggered by blood glucose represents the beta-cells' glucose sensor. Type-2 diabetes mellitus results from insulin resistance in peripheral tissues and impaired insulin secretion. Pathology of diabetic beta-cells might be reflected by the altered morphology of mitochondrial network. Its characterization is however hampered by the complexity and density of the three-dimensional (3D) mitochondrial tubular networks in these cell types. Conventional confocal microscopy does not provide sufficient axial resolution to reveal the required details; electron tomography reconstruction of these dense networks is still difficult and time consuming. However, mitochondrial network morphology in fixed cells can also be studied by 4Pi microscopy, a laser scanning microscopy technique which provides an approximately 7-fold improved axial resolution (approximately 100 nm) over conventional confocal microscopy. Here we present a quantitative study of these networks in insulinoma INS-1E cells and primary beta-cells in Langerhans islets. The former were a stably-transfected cell line while the latter were transfected with lentivirus, both expressing mitochondrial matrix targeted redox-sensitive GFP. The mitochondrial networks and their partial disintegration and fragmentation are revealed by carefully created iso-surface plots and their quantitative analysis. We demonstrate that beta-cells within the Langerhans islets from diabetic Goto Kakizaki rats exhibited a more disintegrated mitochondrial network compared to those from control Wistar rats and model insulinoma INS-1E cells. Standardization of these patterns may lead to development of morphological diagnostics for Langerhans islets, for the assessment of beta-cell condition, before their transplantations. Copyright 2010 Elsevier B.V. All rights reserved.
Keywords: transfekce; zobrazování trojrozměrné; modely nemocí na zvířatech; Mitochondria; Recombinant Fusion Proteins; Insulinoma; Rats, Wistar; Cell Line, Tumor; inzulinom; konfokální mikroskopie; Transfection; techniky in vitro; Diabetes Mellitus, Type 2; potkani Wistar; Imaging, Three-Dimensional; rekombinantní fúzní proteiny; diabetes mellitus 2. typu; Pancreatic Neoplasms; Microscopy, Confocal; krysa rodu Rattus; zelené fluorescenční proteiny; Animals; zvířata; nádory slinivky břišní; beta-buňky; Rats; Disease Models, Animal; Green Fluorescent Proteins; Insulin-Secreting Cells; nádorové buněčné linie; mitochondrie; In Vitro Techniques